Ketersediaan Tempe yang Menerapkan Cara Produksi Pangan yang Baik di Jabodetabek serta Pengetahuan Konsumen untuk Membelinya - Kemal Komala; Ratih Dewanti-Hariyadi; Nur Wulandari (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2024)
Tempe is a nutritious, healthy, and affordable food. Tempe production is simple, but less hygienic under traditional production, therefore can have inconsistent quality, safety, and reduce consumer interest. In Indonesia, Good Manufacturing Practices (GMP) implementation is a basic requirement for food industries, including tempe industries, in producing safe food products. It is yet unknown the availability of GMP tempe, especially in Jabodetabek area and how it relates to consumers' willingness to purchase. This study aimed to determine the availability of GMP tempe in Jabodetabek and to analyze the knowledge, perceptions, and willingness of Jabodetabek consumers to purchase GMP tempe. The research method included observing the GMP-applying tempe availability and surveying consumers' knowledge and willing-ness to purchase GMP-applying tempe using google form questionnaire. Data analysis used descriptive and Spearman correlation test. The results showed that GMP-applying tempe was available in almost half (38%) of market sample in Jabodetabek. GMP-applying tempe was available in small number (1%) of traditional markets and most (72%) supermarkets. Most of the respondents (54%) were used to consuming good quality tempe. Almost all respondents (78%) understood the advantage of GMP-applying tempe. Most respondents (67%) were willing to purchase GMP-applying tempe with a maximum price increase of 20% from regular tempe.